(3MGTjI Ydi dhGeY GdCSQGQs - (3MGLi HGTGs; (3bWH GdOjf GdQGRjs
(3ChdgG (B:s
(3hHYO abO EdJeS efi LeGYI ef CNdU ENhGfi GdGNjGQ Cf CTQM cJGH dhGeY GdGSQGQ ai TQM eWGdY GdGfhGQ ddYGde bWH GdOjf GdQGRi s
(3BNQgG (B:s
(3bhdg hcd eJjSQ deG Ndb dg Gi cd ehab deG Ndb dg gPG BNQ cdGei ai TQM GdTQM hGdMeO ddg Ydi MUhd gPg bHd ahGJ GdhbJ hMdhd GdefjI hGdUdGI Ydi eMeO NjQ GdHQjI hGddg GYde HGdUhGH hEdgj GdeQLY hGdeCH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjag SfI (B784 s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs